RECUENTO DE CÉLULAS SOMÁTICAS EN HATOS LECHEROS DE DIFERENTE NIVEL TECNOLÓGICO EN AREQUIPA - Ortiz Z., César (2012)
The objective of the present studywas to evaluate the Somatic Cell Count (SCC) in milk in dairy herds of theArequipa region.Milk samples were collected every twoweeks throughout the year 2005 from 15 dairy farms located in the irrigated area ofMajes, Santa Rita, and La Joya districts. Milk farms were stratified according to their technological level as high, medium, and low. The average SCCin the studywas 505 x 103 ± 150 x 103 cel/ ml, and for high, medium and lowtechnological level were 353, 559 y 603 x 103 cel/ml, respectively. Significant differences were found between levels of technology (p<0.05). The study showed an increase in SCC as the level of technology in the herd decreased.